Impact of newly measured 26Al(n, p)26Mg and 26Al(n, α)23Na reaction rates on the nucleosynthesis of 26Al in stars. Issue 2 (12th January 2023) - Battino, Umberto; Lederer-Woods, Claudia; Pignatari, Marco; Soós, Benjámin; Lugaro, Maria; Vescovi, Diego; Cristallo, Sergio; Woods, Philip J; Karakas, Amanda
ABSTRACT: The cosmic production of the short-lived radioactive nuclide 26 Al is crucial for our understanding of the evolution of stars and galaxies. However, simulations of the stellar sites producing 26 Al are still weakened by significant nuclear uncertainties. We re-evaluate the 26 Al(n, p) 26 Mg, and 26 Al(n, α) 23 Na ground state reactivities from 0.01 GK to 10 GK, based on the recent n_TOF measurement combined with theoretical predictions and a previous measurement at higher energies, and test their impact on stellar nucleosynthesis. We computed the nucleosynthesis of low- and high-mass stars using the Monash nucleosynthesis code, the NuGrid mppnp code, and the FUNS stellar evolutionary code. Our low-mass stellar models cover the 2–3 M⊙ mass range with metallicities between Z = 0.01 and 0.02, their predicted 26 Al/ 27 Al ratios are compared to 62 meteoritic SiC grains. For high-mass stars, we test our reactivities on two 15 M⊙ models with Z = 0.006 and 0.02. The new reactivities allow low-mass AGB stars to reproduce the full range of 26 Al/ 27 Al ratios measured in SiC grains. The final 26 Al abundance in high-mass stars, at the point of highest production, varies by a factor of 2.4 when adopting the upper, or lower limit of our rates. However, stellar uncertainties still play an important role in both mass regimes. The new reactivities visibly impact both low- and high-mass stars nucleosynthesis and allow a general improvement in the comparison between stardust SiC grains and low-mass star models. Concerning explosive nucleosynthesis, an improvement of the current uncertainties between T9∼0.3 and 2.5 is needed for future studies.